THE QUALITY OF INTERNAL AUDIT'S ROLE, GOOD CORPORATE GOVERNANCE, AND HIGH-QUALITY CORPORATE VALUE: A LITERATURE REVIEW - Fauziyah, Aisyah Nur; Rochayatun, Sulis (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
In this study, the aim is to find out what the role of internal audit is in creating and managing corporate governance to increase quality company value through a review of the results of previous studies. Which method is called a qualitative research method with an approach through literature review or collection and mapping of results from previous researchers? The journals for this research were obtained through Google Scholar and SINTA. Then for the research results obtained, internal audit has a very important role in creating and managing corporate governance. Internal audit will deploy all methods that can improve the quality of corporate governance to increase corporate value. This aims to attract back the interest of creditors and investors and to prevent fraud or cheating.